Integration of HIV-Sexual Reproductive Health Services for Young People and the Barriers at Public Health Facilities in Mbarara Municipality, Southwestern Uganda: A Qualitative Assessment - Akatukwasa, Cecilia; Bajunirwe, Francis; Nuwamanya, Simpson; Kansime, Noel; Aheebwe, Emmanuel; Tamwesigire, Imelda K. (International Journal of Reproductive Medicine, 2019)
Background. Sexual and Reproductive Health (SRH) and HIV risk behaviors for young people are intertwined. This rationalizes the need for integration of HIV and SRH services within the health care system, especially in countries with high HIV burden. In this study, we explored the current status of HIV-SRH integration for young people and barriers of integration from different stakeholders at public health facilities in Mbarara Municipality, southwestern Uganda. Methods. We conducted an exploratory qualitative study at public health facilities in Mbarara district of southwestern Uganda. Data were collected among young people (n=48), health care providers (n=63), and key informants (n=11). We used in-depth interviews and focus group discussions to collect the data. Coding and analysis of qualitative data were done using Atlas.ti. Results. Overall there was no differentiation of HIV-SRH services between adults and young people. Integration of HIV-SRH services was reported at all facility levels; however, there was poor differentiation of services for the young persons and adults. Integrated HIV and SRH services for young people were acknowledged to improve access to information and risk perception, improve continuity of care, and reduce cost of services and would also lead to improved client-health worker relationships. The potential barriers to achieving HIV-SRH integration included individual provider characteristics like lack of training and attitudes, generic health system challenges like low staffing levels, poor infrastructure with lack of space and privacy to deliver these services. At the policy level vertical programing and unclear policies and guidelines were identified as challenges. Conclusion. Our study shows integration of HIV and SRH services exists in general but services for adults and young people are blended or poorly differentiated. Significant health system barriers need to be overcome to achieve differentiation of the services for young people and adults.